131k views
2 votes
If -9(x+3)-2x=-5(2x+3)-4 what is 3x

User GriffonRL
by
5.9k points

1 Answer

6 votes

Answer:

3x = -24

Explanation:


-9(x+3)-2x=-5(2x+3)-4\qquad\text{use distributive property}\\\\(-9)(x)+(-9)(3)-2x=(-5)(2x)+(-5)(3)-4\\\\-9x-27-2x=-10x-15-4\qquad\text{combine like terms}\\\\(-9x-2x)-27=-10x+(-15-4)\\\\-11x-27=-10x-19\qquad\text{add 27 to both sides}\\\\-11x=-10x+8\qquad\text{add 10x to both sides}\\\\-x=8\qquad\text{change the signs}\\\\x=-8\qquad\text{multiply both sides by 3}\\\\3x=-24

User Guye Incognito
by
6.2k points